Health Manpower Forecasting: A systematic Review for Models and Approaches (Bangladesh Journal of Medical Science, 2019)
Background: An appropriate planning requires forecasting the demand and supply of health manpower in an accurate manner.Objectives: The paper objective was to review health manpower forecasting approaches and methods and propose the improvement features for effectiveness of health manpower planning.Data sources: A systematic review was conducted for studies published in English from 1970-2014 using Pub Med, Science Direct, Pro Quest, and Google Scholar databases.Study eligibility criteria: Review articles, qualitative studies, questionnaire driven surveys, retrospective and prospective studies describing or applying various types of forecasting approaches and methods in health manpower forecasting were included in the review.Data collection and study appraisal: Two reviewers (SR and MA) independently appraised the studies to identify relevant ones to be included in the review.Results: A total of 128 studies were included in the review. As a result, two main categories of approaches (conceptual and analytical) for health manpower forecasting were identified with their strengths and weaknesses.Conclusions: Future forecasting methods should benefit from advantages of current approaches and overcome some of their main limitations. Applying a method which incorporates a wide range of factors affecting supply and demand, facilitates the collection of good quality data, monitors changing trends over time, considers the uncertainty of health systems and has a dynamic approach is proposed as an improvement roadmap for future forecasting.Bangladesh Journal of Medical Science Vol.18(3) 2019 p.458-472